Gallic acid potentiates the anticancer efficacy of cisplatin in ovarian cancer cells through modulation of the PI3K/AKT/mTOR and CXCL12/CXCR4 signaling pathways - Liang, Jinlan; Lu, Tingting; Shan, Tiyan; Liang, HuiTing; Wang, Wenjie; Song, Zhijun; Tang, Yong; Wang, Qi (Frontiers in Oncology, 2025)
BackgroundThis study investigates the antitumor effects of gallic acid (GA) on ovarian cancer cells and its potential synergistic therapeutic effects with cisplatin (DDP) through modulation of the PI3K/AKT/mTOR signaling pathway.MethodsSystematic evaluations were conducted using both in vitro cell experiments and in vivo animal models to assess the impact of GA alone and in combination with DDP on ovarian cancer cell proliferation, apoptosis, and related signaling pathways.ResultsThe results demonstrate that GA significantly inhibits the proliferation of ovarian cancer cells and enhances the anticancer effects of DDP by regulating the PI3K/AKT/mTOR signaling pathway. In in vivo experiments, the combination of GA and DDP significantly inhibits tumor growth and prolongs survival in a mouse model of ovarian cancer without apparent toxicity to vital organs.ConclusionThis study provides scientific evidence for the potential use of GA as an adjuvant drug in ovarian cancer treatment.